Sistematización del proyecto de intervención socio - educativo para la prevención de la violencia contra la infancia :Experiencia con los niños, niñas, padres y madres de familia de la escuela Junín de la comunidad Chinchiloma, cantón Cayambe - Guasgua Cabascango, Janneth Marisol (2015)
This project worked with children, fathers and mothers of the "Junín" school, in its first part discusses the theoretical arguments of the issue of violence, they were given at different stages through workshops and worked with beneficiaries, whose aim was to prevent and eradicate violence to achieve. In a second step the results of work carried out with parents, mothers and children are described, is part of a description and characterization of beneficiaries, then place the situation of violence, starting from analyzing the results obtained in Phase Polling and Diagnosis, is, knowing that prospects have about violence and what forms and uses of violence within families are. In the third instance one speaks of the sensitization process to bring the awareness of parents and mothers regarding the treatment of their son / as. To do the work of educational intervention with parents and mothers and intervention with children is mentioned, this content allowed them to achieve emphasize prevention and knowledge of the proper development of social skills. Finally the lesson that places the systematization of this experience doing relation to the commitments generated by parents and mothers and children, after the project, finally the conclusions and recommendations mentioned processes are proposed.